The effect of hypertension in pregnancy and central nervous system anomalies on fetal brain development - Albayrak, Mehmet; Köse, M. Faruk; Anlar, Banu (The European Research Journal, 2023)
Objectives: The aim of this study was to investigate whether maternal hypertension affects fetal brain maturation, and to examine whether treatment with magnesium sulfate has a protective effect on the fetal brain. Methods: A total of 26 fetuses, including 11 dead fetuses of pregnant women who were found to have hypertension and whose pregnancy was terminated due to this reason, and 15 fetuses who did not have this risk factor but died for various reasons as the control group, were included in the study. Brain tissue samples were evaluated for the presence of morphological and histopathological changes, as well as apoptotic cells. The morphologies of the samples were examined in sections stained with hematoxylin-eosin (H&E), and apoptosis was examined with light microscopy by the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) method. Results: In the control group, it was observed that the brain tissue had a morphological structure compatible with the development weeks. In the hypertension group, there were no bleeding foci and brain tissues mostly preserved morphological features similar to control patients. While edema was detected in 45.4% of the infants in the hypertension group, no edema was observed in 54.6%. In the hypertension group, Grade 1 necrosis was observed in 63.6% of the samples, Grade 2 necrosis was observed in 9.1%, and no necrosis was observed in 27.3% of the samples. Conclusions: Based on the findings of this study, it can be concluded that maternal hypertension increases neurological maturation by causing vasodilation in the fetal brain, increasing blood flow, and decreasing cell death.